Are Gestures of One Culture the Same as Those of the Another One? In the Search of Cross-Cultural Differences in Nonverbal Behaviour from the Perspective of Cognitive Linguistics - Czubak-Wróbel, Paulina (Glottodidactica, 2008)
From all the examples of nonverbal behaviour it has been scientifically proved that gestures reflect human thoughts and mental operations. Gestures project meanings that are stored in image schemas. Those mental representations are shaped by culturally determined experience. The aim of this article was to delve into the issue of the cross-cultural differences in nonverbal behaviour with the par-ticular focus on gestures from the point of view of cognitive linguistics. It was also of my interest to identify and categorise gestures as regards their universal and/or culture specific nature and create a background for possible further research.